KARAKTERISASI KEKERASAN DAN STRUKTUR MIKRO BAJA AISI 410 PADA PROSES TEMPERING DENGAN VARIASI MEDIA PENDINGIN - Jamaludhin Rais; Sunardi Sunardi; Erny Listijorini (Jurusan Teknik Mesin Fakultas Teknik Universitas Jember, 2020)
In AISI 410 steel, the characteristic changes observed in this study were the value of hardness, and microstructure shape. Material samples heated on temperature 9000C and held for 45 minutes, with cooling medium variation used are water, used oil, and SAE 20W-50 oil. In the process, tempering the material sample returns heated on 3000C and held for 15 minutes, then cooled in the room open. The results showed that the microstructure formed in AISI 410 steel after heat treatment is martensite lath, ferrite and austenite. From the results has been obtained, that the quenching process with a variety of cooling media used and followed by the tempering process can affect the shape of the microstructure of AISI 410 steel, changes that occur are increase in the hardness value of the material. The results showed that the sample quenching water had the highest hardness is 378 HV, followed by quenching of SAE 20W-50 oil and used oil with grades of 377 and 362 HV, respectively. The increase in hardness value occurs due to changes in the micro structure that occur due to the heat treatment process. The increase in the value of hardness that occurred in the material was 143.7%.